PENGARUH AKTIVITAS FISIK TERHADAP RISIKO OBESITAS PADA USIA DEWASA - Rivan Virlando Suryadinata; Devitya Angielevi Sukarno (Universitas Airlangga, 2019)
Indonesia has an increasing number of obese people every year. Risk factors and complications caused by obesity can increase morbidity and mortality in the community. One of factors causing the increasing number of obese people is caused by the decreasing level of physical activities done by Indonesian people.This study aims to determine the effect of physical activity levels on the risk of obesity. The study used an observational analytic case control design. Subjects were chosen through a purposive sampling method. The population was young adults in Surabaya. The sample of the study included 97 obese adults and 97 non-obese adults. The study was conducted in March - July 2018 in South Surabaya through distributing questionnaires to two groups. The questionnaire given used the Global Physical Activity Questionnaire (GPAQ). The results showed that physical activity performed by adult age group of obesity was mostly classified as low activity (59,8%), while non-obese adult age group was mostly included in medium activity (56,6%).This shows a significant difference in physical activity between obese and non-obese groups (p=0,047). It can be concluded that decreased levels of physical activity may increase the risk of obesity in adult.